KINERJA DINAS KETENAGAKERJAAN DALAM PELAKSANAAN PELATIHAN DAN PENINGKATAN PRODUKTIVITAS TENAGA KERJA DI KOTA PEKANBARU TAHUN 2022 - Wahyuandra, Muhammad Ilham; ', Muchid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
In the employment program, the Manpower Department carries out activities that function to improve the quality of the workforce in implementing the program. Two programs implemented by the Pekanbaru City Manpower Office are the Workforce Quality and Productivity Improvement Program and the Job Opportunities Increase Program. However, in the implementation of the Pekanbaru City Manpower Service's employment program, there are problems such as 1) Lack of socialization regarding the existence of the Pekanbaru City Manpower Service's employment program, and 2) Training and apprenticeships held by the Pekanbaru City Manpower Service do not absorb much of the ready-to-use workforce. . A large number of job seekers are not absorbed in the implementation of the Pekanbaru City Manpower Office employment program. This type of research is descriptive qualitative with data collection techniques through interviews, observation and documentation. The results of the research found that the Pekanbaru City Manpower Department in improving the quality of the workforce is still not optimal. This is demonstrated by the lack of quality and quantity of employees with special skills, limited facilities and infrastructure as well as the availability of budget to carry out outreach. The job training program implemented by the Pekanbaru City Manpower Office has not been able to completely change the social conditions of the training participants. Only 45.3% of the training participants worked or opened a business after the training. And only 44.2% of them work or open a business according to the field of training they are participating in. The factors that hinder the Pekanbaru City Manpower Service in improving the quality of the workforce in Pekanbaru City are: 1) There is still a lack of human resources capable of providing training materials, they still rely on assistance from the private sector because internally the Pekanbaru City Manpower Office is still unable to provide its own instructors. . 2) The availability of facilities and infrastructure is still minimal. 3) Limited budget for socialization. 4) The interest and intentions of training participants are still low. Keywords: Performance, Quality, Labor